2020
DOI: 10.1097/prs.0000000000006385
|View full text |Cite
|
Sign up to set email alerts
|

Genital Gender-Affirming Surgery in Transgender Men in The Netherlands from 1989 to 2018: The Evolution of Surgical Care

Abstract: Background: The number of individuals with gender identity incongruence seeking treatment, including genital gender-affirming surgery, has increased over the past decade. Surgical techniques for genital gender-affirming surgery in transgender men have evolved considerably. The aim of this study was to present an overview of the evolution of genital gender-affirming surgery for transgender men in a single, high-volume center. Methods: The authors perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 39 publications
0
15
0
1
Order By: Relevance
“…1 The number of transgender men opting for gGAS has increased significantly over the last decade in our center, from an average of 11 per year before 2011, to an average of 22 per year since 2015. 2 Depending on personal preference, expectations, and physical characteristics, a phalloplasty or metoidioplasty is performed. The importance of voiding out of the tip of the phallus makes gGAS with urethral lengthening (UL) an important treatment option.…”
Section: Introductionmentioning
confidence: 99%
“…1 The number of transgender men opting for gGAS has increased significantly over the last decade in our center, from an average of 11 per year before 2011, to an average of 22 per year since 2015. 2 Depending on personal preference, expectations, and physical characteristics, a phalloplasty or metoidioplasty is performed. The importance of voiding out of the tip of the phallus makes gGAS with urethral lengthening (UL) an important treatment option.…”
Section: Introductionmentioning
confidence: 99%
“…Admittedly, there is considerable heterogeneity in the surgical techniques used and how to classify complications. This makes it hard to compare techniques and even make comparisons with phalloplasty outcomes, for those patients who are weighing the risks of each procedure [13,14] . When patients request a metoidioplasty, we believe that they are seeking the most reliable technique for standing to void, with the least recovery and scar burden.…”
Section: Discussionmentioning
confidence: 99%
“…2e9 At this moment, transmen have a higher variety of surgical options than trans women with regard to genital genderaffirming surgery. 10,11 The reproductive organs can be removed, and the external genital can be masculinized in various different ways. Each option comes with different physical requirements, expected outcomes, and risk of complications.…”
Section: Introductionmentioning
confidence: 99%
“…1,14e17 Over the past decades, major improvements in surgical approaches have been made, and follow-up studies repeatedly show positive effects on psychosocial outcomes. 10,18 At the same time, despite extensive preoperative counseling, postoperative satisfaction varies, which has partially been attributed to a mismatch between expectations and surgical outcomes in certain individuals. 14,15,19,20 Numerous studies showed that decision aids (DAs) improve the patients' ability to make an informed choice by enhancing the patients' knowledge and participation in the process, help create more realistic expectations of potential benefits and harms of treatment, and support patients to make a decision as per their informed values.…”
Section: Introductionmentioning
confidence: 99%